Hubungan Antara Tingkat Kecemasan dengan Insomnia pada Siswa di SMA Negeri 03 Batam - Nopri Esmiralda; Suryanti Suryanti; Reka Handayani (Zona Kedokteran: Program Studi Pendidikan Dokter Universitas Batam, 2022)
Background: Anxiety that is often experienced by teenagers is usually related to the learning process at school. Anxiety can appear as a physiological response to anticipate a problem that may come or appear as a disturbance if it arises excessively. Insomnia is a symptom that refers to complaints of difficulty falling asleep, frequent or prolonged awakening, inadequate sleep quality, or short overall sleep duration in individuals who have sufficient time available for sleep. This study aims to determine the correlation between anxiety levels and insomnia on students at SMA Negeri 03 Batam. Method: This is an observational analytic research using a cross-sectional approach conducted at the SMA Negeri 03 Batam in December 2021. A total of 160 students were analyzed through a simple random sampling method. The research instrument used the Zung Self-Rating Anxiety Scale (ZSAS) to evaluate anxiety and the Insomnia Rating Scale (IRS) to evaluate insomnia. To determine the correlation between anxiety levels and insomnia on students, an analytical test was conducted by spearman test. Result: The results of the Spearman test showed that there was a significant relationship between the level of anxiety and insomnia on students with a p value = 0.000 (p <0.05). Conclusion: Based on the results of this study, it can be concluded that there is a correlation between the level of anxiety and insomnia on students of SMA Negeri 03 Batam.